DOC PREVIEW
Stanford CS 157 - Lecture 15 - Equality

This preview shows page 1-2-14-15-29-30 out of 30 pages.

Save
View full document
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
View full document
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience
Premium Document
Do you want full access? Go Premium and unlock all 30 pages.
Access to all documents
Download any document
Ad free experience

Unformatted text preview:

EqualityComputational LogicLecture 16Michael GeneserethSpring 20022CoreferentialityDifferent terms can sometimes refer to the same object.2+22*24In many situations, we want to say explicitly that two terms arecoreferential; and, in many situations, we want to sayexplicitly that two terms are not coreferential. For this, we useequality2+2=2*2Coreferentiality3EqualityAn equation is true if and only if the terms in the equation referto the same object in the universe of discourse.(1) Given an interpretation, a constant “refers” to the node inthe interpretation graph on which it occurs as a label.(2) Given an interpretation, a functional term refers to thevalue of the function applied to the arguments as specified inthe interpretationInterpretation/Database:{boss(art)=art,boss(joe)=art}Example:p(x,boss(x)) → p(joe,boss(joe)) → p(joe,art).4HerbrandThe Herbrand Theorem does not hold in the presence ofequality.In a Herbrand interpretation, every constant refers toitself. In other interpretations, different constants mayrefer to the same constant.5IncompletenessTheorem: Resolution (with factoring) is refutationcomplete for Relational Logic*.*without equality.Theorem: There is a set of premises ∆ and a conclusion ϕ(involving equality) such that ∆ logically implies ϕ but ϕcannot be proved from ∆ using Resolution.1. b = aPremise2. b = cPremise3. a = c? Goal6Two ApproachesAxiomatic approach -- add axioms of equalityProof Theoretic approach -- add new rules of inference7Equality AxiomsReflexivity∀x.x=xSymmetry:∀x.∀y.(x=y ⇒ y=x)Transitivity:∀x.∀y.∀z.(x=y ∧ y=z ⇒ x=z)8Equality Axioms in Rule FormReflexivityx=xSymmetry:x=y ⇐ y=xTransitivity:x=z ⇐ x=y ∧ y=z9Equality Proof1. b = aPremise2. b = cPremise3. x = x Equality4. x = y ⇐ y = x Equality5. x = z ⇐ x = y ∧ y = z Equality6. a = c? Goal7. a = y ∧ y = c? 5,68. y = a ∧ y = c? 4,79. b = c? 1,810. ? 2,910Equality Problem1. f(a) = bPremise2. f(b) = aPremise3. x = x Equality4. x = y ⇐ y = x Equality5. x = z ⇐ x = y ∧ y = z Equality6. f( f (a)) = a? Goal7. a = f ( f (a))? 4,68. f( f (a)) = y ∧ y = a? 5,69. f( f (a)) = w ∧ w = y ∧ y = a? 5,810. f( f (a)) = v ∧ v = w∧ w = y ∧ y = a? 5,911FlatteningEquivalence:f(f(a))=a ⇔ ∃x.(f(a)=x ∧ f(x)=a)Rewrite: f(f(a))=aAs: ∃x.(f(a)=x ∧ f(x)=a)As: f(a)=c ∧ f(c)=aAs: f(a)=c f(c)=aRewrite: f(f(a))=a?As: ∃x.(f(a)=x ∧ f(x)=a)?As: f(a)=x ∧ f(x)=a?12Proof With Flattening1. f (a) = bPremise2. f (b) = aPremise3. x = x Equality4. x = y ⇐ y = x Equality5. x = z ⇐ x = y ∧ y = z Equality6. f (a) = x ∧ f (x) = a? f( f (a)) = a?7. f (b) = a? 1,68. ? 2,713Substitution AxiomFlattening Rule:f(f(a))=a ⇔ ∃x.(f(a)=x ∧ f(x)=a)Substitution Axiom:f(x)=z ⇐ x=y ∧ f(y)=z14Proof With Substitution1. f(a) = bPremise2. f(b) = aPremise3. x = x Equality4. x = y ⇐ y = x Equality5. x = z ⇐ x = y ∧ y = z Equality6. f(x) = z ⇐ x = y ∧ f (y) = z?Substitution7. f( f (a)) = a? Goal8. f(a) = y ∧ f (y) = a? 6,79. f(b) = a? 1,810. ? 2,915NotesSubstitution axioms for relation constants too.p(x) ⇐ x=y ∧ p(y)Substitution axioms for multiple argumentsp(x,y)=z ⇐ x=u ∧ y=v ∧ p(u,v)Need one substitution for each function and relation constant.16Motivation for Demodulationp(a, f (b,g(a,h(b)),c),d)b = ep(a, f (b,g(a,h(e)),c),d)17Demodulation{ϕ1,...,ϕn}{τ1= τ2}{ϕ1,...,ϕn}[τ1σ ←τ2σ]where τ occurs in ϕi where τ1σ = τ18Examplesp(a, f (b,g(a,h(b)),c),d)b = ep(a, f (e,g(a,h(e)),c),d)p(a, f (b,g(a,h(b)),c),d)g(x, y) = j(x)p(a, f (b, j(a),c),d)19Non-Examplesp(a,g(a,b),c)g(a,y) = y ⇐ p(y)p(a,g(a,b),c) ⇐ p(b)p(a,g(x,b),c)g(a,y) = j(y)p(a, j(b),c)Unit Equations OnlyVariables Substituted in Equation Only20Parent DeletionIn general, given a literalwith n arguments and k equations:Demodulation at most 1 clauseParamodulation (k+1)n possible clauses1. a = 1 a = 12. p(a,a,a) p(a,a,a)3. p(a,a,1) p(a,a,1)4. p(a,1,1) p(a,1,a)5. p(1,1,1) p(a,1,1)6. p(1,a,a)7. p(1,a,1)8. p(1,1,a)9. p(1,1,1)In Demodulation, parent is usually deleted after substitution.21Proof With Demodulation1. f (a) = bPremise2. f (b) = aPremise3. x = x Equality4. f ( f(a)) = a? Goal5. f (b) = a? 1,46. ? 2,522Proof With Demodulation1. f(1) =1Premise2. f(x) = x* f(x −1)Premise3. x = x Equality4.arithmeticaxiomsPremise5. f(3) = z? Goal6. 3* f (3−1) = z? 2,57. 3* f (2) = z? 4,68. 3*2* f(2 −1) = z? 2,79. 3*2* f(1) = z? 4,810. 3*2*1= z? 1,911. 3*2 = z? 4,1012. 6 = z? 4,1113. ? 3,1223Proof With DemodulationSuppose Bill is Joe's paternal grandfather and suppose that Billis kind. Prove that Joe's paternal grandfather is kind.1. pgf (joe) = billPremise2. f ( f(x)) = pgf (x)Premise3. kind(bill)Premise4. kind( f ( f (joe)))? Goal5. kind(pgf( joe))? 2,46. kind(bill)? 1,57. ? 3,624Problems With DemodulationCannot bind variables in expression:father(pat) =quincyolder( father(x), x)older(quincy,pat)Equation must be a unit clausefather(x) = y ⇐ x = pat ∧ y =quincyolder( father(x), x)older(quincy,pat) ⇐ x = pat ∧ y =quincy25Paramodulation{ϕ1,...,ϕn}{ψ1,...,τ1= τ2,...,ψn}{ϕ1,...,ϕn,ψ1,...,ψn}σ[τ1σ ← τ2σ]where τ occurs in ϕi where τ1σ = τσ26Differences(1) Demodulation requires a unit equation.(2) Demodulation binds variables in equation only.(3) Demodulation deletes parent.27Example{p( f (x,b),x),q(x)}{f (a,y) = y,r(y)}{p(b,a),q(a),r(b)}28Proof With Paramodulation1. {father(pat) =quincy}Premise2. {older( father(x),x)}Premise3. {¬older(quincy,pat)} Goal4. {older(quincy, pat)} 1,25. {} 3,429Proof With Paramodulation1. {p(a)}Premise2. {p(b)}Premise3. {a = c,b = c} a = c∨ b = c4. {¬p(c)} Goal5. {¬p(a),b = c} 3,46. {¬p(a),¬p(b)} 4,57. {¬p(b)} 1,68. {} 2,730PowerTheorem: Resolution and Paramodulation (together with thereflexivity axiom) are refutation complete for all of RelationalLogic*.*including


View Full Document

Stanford CS 157 - Lecture 15 - Equality

Documents in this Course
Lecture 1

Lecture 1

15 pages

Equality

Equality

32 pages

Lecture 19

Lecture 19

100 pages

Epilog

Epilog

29 pages

Equality

Equality

34 pages

Load more
Download Lecture 15 - Equality
Our administrator received your request to download this document. We will send you the file to your email shortly.
Loading Unlocking...
Login

Join to view Lecture 15 - Equality and access 3M+ class-specific study document.

or
We will never post anything without your permission.
Don't have an account?
Sign Up

Join to view Lecture 15 - Equality 2 2 and access 3M+ class-specific study document.

or

By creating an account you agree to our Privacy Policy and Terms Of Use

Already a member?